Bidang Kerja dan Sistem Komunikasi Sourcing Planning Pcd di Toyota Motor Manufacturing Indonesia Karawang Plant 1 & 2 - Agung Yesaya Rajagukguk; Ibrahim Lammada; Rahmat Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2023)
The development of the industry is currently very rapid, there are many technologies that have been found, so students are required to have experience working directly in the field to adapt to technological changes that occur. Toyota Motor Manufacturing Indonesia (TMMIN) was chosen by the author as the place of practical work because TMMIN is the largest automotive industry and manufacture in Indonesia. The purpose of this practical work is to provide work experience to students by working directly in an industry, preparing graduates who are ready to work professionally, have a work ethic and in accordance with the demands of the world of work, maintain good relations between universities and industry, train themselves to always ready to be placed wherever later when plunging into the real world of work, Studying work fields, flow and communication systems at SP – PCD TMMIN. The author is placed in the Sourcing Planning section and the Production Control division, from the practical work carried out, the author gains insight into the field of work and communication systems that exist in Sourcing Planning as the section that takes care of the flow of parts supply in the production process and takes care of some work related to production.